The orientation of a decellularized uterine scaffold determines the tissue topology and architecture of the regenerated uterus in rats†. Issue 5 (14th January 2019) - Miki, Fumie; Maruyama, Tetsuo; Miyazaki, Kaoru; Takao, Tomoka; Yoshimasa, Yushi; Katakura, Satomi; Hihara, Hanako; Uchida, Sayaka; Masuda, Hirotaka; Uchida, Hiroshi; Nagai, Toshihiro; Shibata, Shinsuke; et al.
Abstract: A decellularized uterine scaffold (DUS) prepared from rats permits recellularization and regeneration of uterine tissues when placed onto a partially excised uterus and supports pregnancy in a fashion comparable to the intact uterus. The underlying extracellular matrix (ECM) together with an acellular, perfusable vascular architecture preserved in DUS is thought to be responsible for appropriate regeneration of the uterus. To investigate this concept, we examined the effect of the orientation of the DUS-preserving ECM and the vascular architecture on uterine regeneration through placement of a DUS onto a partially defective uterine area in the reversed orientation such that the luminal face of the DUS was outside and the serosal face was inside. We characterized the tissue structure and function of the regenerated uterus, comparing the outcome to that when the DUS was placed in the correct orientation. Histological analysis revealed that aberrant structures including ectopic location of glands and an abnormal lining of smooth muscle layers were observed significantly more frequently in the reversed group than in the correct group (70% vs. 30%, P  < 0.05). Despite the changes in tissue topology, the uteri regenerated with an incorrectly oriented DUS could achieve pregnancy in a way similar to uteri regenerated with a correctly oriented DUS. These results suggest that DUS-driven ECM orientation determines the regenerated uterus structure. Using DUS in the correct orientation is preferable when clinically applied. The disoriented DUS may deteriorate the tissue topology leading to structural disease of the uterus even though the fertility potential is not immediately affected. Abstract : The disoriented placement of a decellularized uterine scaffold onto a partially defective uterine area results in the regeneration of uterus with aberrant structures including ectopic location of glands and an abnormal lining of smooth muscle layers in rats.